2013
DOI: 10.1186/1297-9716-44-90
|View full text |Cite
|
Sign up to set email alerts
|

Potential of recombinant inorganic pyrophosphatase antigen as a new vaccine candidate against Baylisascaris schroederi in mice

Abstract: The intestinal nematode Baylisascaris schroederi is an important cause of death for wild and captive giant pandas. Inorganic pyrophosphatases (PPases) are critical for development and molting in nematode parasites and represent potential targets for vaccination. Here, a new PPase homologue, Bsc-PYP-1, from B. schroederi was identified and characterized, and its potential as a vaccine candidate was evaluated in a mouse challenge model. Sequence alignment of PPases from nematode parasites and other organisms sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Inorganic pyrophosphatases (PPases) are pivotal in the development of the larval stages of several nematodes, and one homologue of PPases (Bsc-PYP-1) from B. schroederi has been identified. Its antigenicity has been demonstrated, and it may be considered a vaccine candidate against baylisascariasis (144). Considering the demonstrated homology and potential cross-antigenicity of PPases from other ascarid species, it is possible that this or other PPases will be identified as candidates for the development of vaccines against B. procyonis (144).…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Inorganic pyrophosphatases (PPases) are pivotal in the development of the larval stages of several nematodes, and one homologue of PPases (Bsc-PYP-1) from B. schroederi has been identified. Its antigenicity has been demonstrated, and it may be considered a vaccine candidate against baylisascariasis (144). Considering the demonstrated homology and potential cross-antigenicity of PPases from other ascarid species, it is possible that this or other PPases will be identified as candidates for the development of vaccines against B. procyonis (144).…”
Section: Prevention and Controlmentioning
confidence: 99%
“…As with other ascaridoids, adult B. schroederi usually inhabit the intestines of the giant panda, while the larvae may disseminate into various body tissues. In pandas, damage to bodily tissues includes extensive inflammation and scarring of the intestinal wall and parenchyma of the liver and lung (also known as visceral larval migran, VLM; caused by larvae), as well as intestinal obstruction, inflammation, and even death (caused by adults) [ 5 - 8 ]. Currently, diagnosis and identification of B. schroederi infection in pandas relies on morphological examination of fecal eggs, which requires extensive expertise and is difficult, laborious, and prone to error (as the density of eggs in bamboos-enriched feces is low and subject to possible environmental cross-contaminating with the eggs of other parasites, including morphologically similar Baylisascaris spp.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, aside from these immunogens, more attention has focused on targets that play essential roles in the survival of the parasite. For example, Xie et al (2013) identified PYP-1, a new homologue of inorganic pyrophosphatases (PPases) (Kajander et al, 2013), which likely plays critical roles in nematode development and moulting (Islam et al, 2003;Ko et al, 2007) and is distributed widely in the body wall, gut epithelium, ovary and uterus of adult female Baylisascaris. Two separate vaccination experiments in mice (BALB/c) showed that recombinant PYP-1 induced 69%-71% reductions in the number of liver-stage and lung-stage larvae 7 days following challenge infection (Xie et al, 2013).…”
Section: Treatment and Controlmentioning
confidence: 99%
“…For example, Xie et al (2013) identified PYP-1, a new homologue of inorganic pyrophosphatases (PPases) (Kajander et al, 2013), which likely plays critical roles in nematode development and moulting (Islam et al, 2003;Ko et al, 2007) and is distributed widely in the body wall, gut epithelium, ovary and uterus of adult female Baylisascaris. Two separate vaccination experiments in mice (BALB/c) showed that recombinant PYP-1 induced 69%-71% reductions in the number of liver-stage and lung-stage larvae 7 days following challenge infection (Xie et al, 2013). An investigation of the IgG subclasses in the sera of immunised mice showed that the level of IgG1 was significantly higher than IgG2a, with increased levels of IL-4 and IL-10, indicating a type 2 protective immune response (Xie et al, 2013).…”
Section: Treatment and Controlmentioning
confidence: 99%
See 1 more Smart Citation